Enhancing Nutritional, Physical, and Organoleptic Properties of African Catfish (Clarias gariepinus) Floss by Adding Cowpea (Vigna unguiculata subsp. Cylindrica) Filler - Amalya Nurul Khairi; Nur Hafizah Amriyanti (Food ScienTech Journal, 2025)
Floss meat generally experiences shrinkage due to the long cooking process so that it loses a lot of weight and nutrition. It is necessary to look for alternatives to reduce the loss, such as adding functional fillers. Catfish as an energy resource content of protein 15.70%, fat 8.38%, calcium 8.01 mg/100 g, phosphorus 4.18 mg/100 g, and iron 203 mg/100 g. Cowpeas have a source of protein 25.38 g/100 g, carbohydrates 57.12 g/100 g, starch content of 30.9-34.9% and classified as high protein and high carbohydrates material. The aim of this research was to determine the effect of adding cowpea fillers on the physicochemical and organoleptic properties of catfish floss. This research used a Completely Randomized Design (CRD) with one obtained, namely F0 (100% catfish), F1 (25% catfish : 75% cowpeas), F2 (50% catfish : 50% cowpeas), F3 (75% catfish : 25% cowpeas). Research stages include making samples, analysing physical properties including yield and pH, chemical analysis including moisture content, ash content, dissolved protein, total protein, crude fiber content, fat content, carbohydrates. Organoleptic tests are descriptive and hedonic. The research data was analysed using the one way anova test and if there was a significant difference at the 5% level then continued with the Duncan test. The result of this research show that catfish floss with the addition of cowpea filler has a yield value of 75.22-114.44; pH 5.07-5.19; water content 1.78-4.40%; ash content 2.73-2.98%; soluble protein 1.46-1.98%; total protein 15.35-25.36%; crude fiber 2.70-11.42%; fat 29.50-43.29%; carbohydrates by different 30.82-47.19%. The result of the hedonic organoleptic test showed the panellists liked catfish floss with the addition of cowpea filler including smell and taste parameters, whereas color and texture parameters were preferred without cowpea. The descriptive organoleptic test of floss meat has a non-fishy smell, yellow color, tastes like cowpeas and catfish meat, and has a slightly rough texture.